V's Virtual Afterlife - Jasmyn Connell; Christopher Moore; Reneé Middlemost (Persona Studies)
Nonhuman Online Personas (NHOPs) are coherent digital assemblages not directly associated with the identities of individual humans. NHOPs encompass entities like brands, places, artificial intelligences, and, as we explore in this study, video game characters. This article examines the NHOP of V, the customisable protagonist from the video game Cyberpunk 2077, to consider how such characters attain a virtual afterlife beyond the original text through collective fan engagement. We propose ‘persona analysis’ as a novel qualitative case study methodology for researching NHOPs. Our approach integrates netnography, analytic autoethnography and textual analysis, enabling a comprehensive examination of the emergent, unpredictable, and collective natures of online personas. Building on existing persona studies frameworks, we focus on the collective dimension of persona as the sets of negotiations between human and nonhuman actors through which the NHOP is constructed. Using V as a case study, we apply the five dimensions of persona—mediatisation, publicness, performance, collective, and value—to analyse the NHOP. Data was collected from online platforms where fan productions occur, including fan fiction, game mods, virtual photography, conversation, and discussion. This multi-platform approach allowed us to observe the extensive participatory practices of fans' co-construction of V’s NHOP with its developers. Our analysis reveals that V’s NHOP is a complex, rhizomatic assemblage resulting from the participatory interplay between in-game characters, fans, games designers, developers, the storyworld’s creators, and intellectual property owners. By extending persona studies to encompass NHOPs, this research contributes to a deeper understanding of how online personas are collectively constructed. This, in turn, challenges established notions of online identity grounded in selfhood and opens new possibilities for examining the co-creation of online personas across all media types.